Improvement of Physics Learning Outcomes by Applying Discovery Learning Models in Vocational Vibration and Waves - Florentina Maria Panda; Albert Lumbu; Elisabet Kuneb (Jurnal Pembelajaran Fisika, 2019)
Research has been conducted with the aim to find out an increase in learning outcomes by using the discovery learning model of student learning outcomes. This type of research is quantitative with pre-experimental design research methods. The research design used was one-group pretest-posttest. The study was conducted at Jayapura 11 Public Middle School in the 2018/2019 school year. The sample used in this study was class VIIIC, amounting to 30 students. The analysis technique used is the n-gain analysis. The results of research and data processing obtained that there is an increase in student learning outcomes in class VIIIC 11 State Junior High School Jayapura namely the average n-gain value for the vibration concept of 0.65, the wave concept obtained an average n-gain is 0.67, whereas in the concept transverse waves and longitudinal waves, increasing student learning outcomes obtained an average n-gain of 0.69. Based on the learning outcomes of each concept seen an increase but each of these concepts is in the medium category taught by the discovery learning model. Normalized n-gain results for the whole concept are included in the medium category where n-gain is obtained 0.67.